2003
DOI: 10.1038/sj.jp.7210871
|View full text |Cite
|
Sign up to set email alerts
|

Perinatal/Neonatal Case Presentation: Neonatal Acute Renal Failure Secondary to Maternal Exposure to Telmisartan, Angiotensin II Receptor Antagonist

Abstract: Fetal and neonatal toxic effects of angiotensin II receptor antagonists have been described in animals and humans. Five cases of fetal or neonatal deaths have been reported following maternal use of sartans for hypertension. We report a case of neonatal transient renal failure following telmisartan therapy during pregnancy. This class of antihypertensive drugs should be avoided during pregnancy and breastfeeding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 7 publications
0
18
0
1
Order By: Relevance
“…Three trials [22,24,29] investigated add-on therapy of ARAs with ACEi and with proteinuria as the primary parameter (n= 19). We also found 12 articles about AEs [31][32][33][34][35][36][37][38][39][40][41][42], eight of which reported embryotoxic effects of ARAs given during [31][32][33][34][35][36][37][38], whereas one other was a pharmacokinetic study without efficacy data [43] .…”
Section: Study Characteristicsmentioning
confidence: 96%
See 1 more Smart Citation
“…Three trials [22,24,29] investigated add-on therapy of ARAs with ACEi and with proteinuria as the primary parameter (n= 19). We also found 12 articles about AEs [31][32][33][34][35][36][37][38][39][40][41][42], eight of which reported embryotoxic effects of ARAs given during [31][32][33][34][35][36][37][38], whereas one other was a pharmacokinetic study without efficacy data [43] .…”
Section: Study Characteristicsmentioning
confidence: 96%
“…There was no retardation in growth and development. Pietrement et al [36] reported a newborn baby whose mother had been taking telmisartan (40 mg/day) until the 33rd week of gestation. Two days postpartum, the baby had acute renal failure, which normalized on the third day.…”
Section: Aesmentioning
confidence: 98%
“…Two neonates had acute renal failure after birth after exposure to either candesartan or telmisartan until delivery. Both patients recovered without sequelae, but long-term follow-up was not reported [19,20].…”
Section: Commentarymentioning
confidence: 70%
“…Among those literature reports describing the gestational age, substance used, period of medication intake (gestational trimester) and outcome of the single cases, we identified 34 literature reports 7-40 describing pregnant women who took ARBs on and after GW 13. Among these 34 literature reports, single cases were described in 24 literatures reports, [8][9][10][11][12][13][14]16,17,[19][20][21][22][25][26][27][28]31,33,34,[36][37][38][39] two cases (including one set of twins 15 ) in four reports, 15,18,24,32 three cases in one report, 23 four cases in one report, 30 five cases in one report, 29 seven cases in one report, 7 20 cases in one report 35 and 45 cases in one report. 40 Thus, information was obtained from these 34 reports regarding the clinical courses of 116 fetuses whose mothers took ARBs on and after GW 13.…”
Section: Methodsmentioning
confidence: 98%